La mise en œuvre des principes de flexibilité de la pédagogie universelle : une étude de cas en contexte universitaire québécois - Desmarais, Marie-Élaine; Rousseau, Nadia; Stanké, Brigitte (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
The heterogenization of Quebec university students raises several challenges (Vagneux & Girard, 2014), including the exclusivity of access to specialized services for diagnosed students. Universities must find solutions that meet the diverse educational needs of all their students while maintaining their high standards (Macé & Landry, 2012) without forcing students to present diagnostic evidence. Universal Design for Learning, by its flexibility, appears promising since it considers this diversity differently than by a diagnosis (Orr & Bachman Hammig, 2009). This case study aims to understand better the process of implementing Universal Design for Learning for Quebec academics. The results, from interviews and observations, describe the stages of this implementation as well as the educational strategies deployed. This study offers concrete solutions to support universities in responding collectively and flexibly to the varied educational needs of all their students. Keywords: case study, denormalization, disability studies, inclusive practice, universal design for learning